Dizziness in discus throwers is related to motion sickness generated while spinning - Perrin, P.; Perrot, C.; Deviterne, D.; Ragaru, B.; Kingma, H. (Acta Oto-Laryngologica, 2000)
While both discus and hammer throwing involve rotating movements resulting in the throw of an object, discus throwers sometimes report dizziness, a condition never experienced by hammer throwers. We investigated whether this susceptibility was related to the sensitivity of the thrower or to the type of throwing achieved. For the latter, we compared the determining features of gesture, gaze stabilization and projectile trajectory in both sports. A total of 22 high-level sportsmen in these 2 disciplines, half of them practising both sports, were interviewed. Slow motion video recordings of discus and hammer throwing were examined to determine the visual referential, head movements and plantar surface support area involved at each stage of the motions. Discomfort was reported by 59% of the sportsmen while throwing discus, but by none while throwing hammer. Because several individuals practised both sports, these results exclude the hypothesis of individual susceptibility to dizziness. Video analysis evidenced that during hammer throwing, visual bearings can be used more easily than during discus throwing. Moreover, there is a loss of plantar afferents and generation of head movements liable to induce motion sickness, such as Coriolis acceleration. In conclusion, although hammer and discus-throwing present numerous similarities, we demonstrate here that crucial differences in the specific execution of each sport are responsible for the dizziness experienced by discus throwers. Acta Otolaryngol 2000 Mar;120(3):390-5